Placental Expression of the Forelimb Patterning Transcription Factor MEIS2 in Trisomy 15. (2nd November 2021) - Pors, Jennifer; Philipp, Tom; Terry, Jefferson
Abstract: Background Observations of first trimester human trisomy 15 (T15) embryos have identified meromelic changes in the upper limbs. These changes are similar to those observed in animal studies investigating the effects of overexpression of Meis2, a signaling transcription factor expressed during forelimb development. Although it would be exceedingly difficult to assess MEIS2 expression in the human embryonic arm, MEIS2 has been reported as consistently expressed in first trimester placental villus stroma. Methods: This study addresses whether gene dosage effect might underlie meromelia in T15 by comparing MEIS2 expression in placentas from T15 and euploid spontaneous abortions employing manual and automated assessment of MEIS2 immunohistochemical scoring. Results: Average MEIS2 expression is increased in T15 first trimester placental tissue compared to euploid controls but that the difference is marginal. Manual and automated scoring showed moderately strong correlation. Conclusion: Extrapolation of these results suggests MEIS2 overexpression may not be required for meromelia in T15.